Quality of duodenal-pancreatectomy according to international standards. Can we achieve them in Uruguay? Preliminary results of a new HPB surgical team at a teaching center. - Castro, Álvaro; Soumastre, Alejandro; Berhouet, Facundo; Prestes, Jimena; Murias, Federico; Curi, Jorge; González, Fernando (Cirugía del Uruguay, 2025)
Introduction. Uruguay, has a low demographics, so there is a low number of complex surgical pathologies for each health center. Objective. To evaluate the results of duodenum-pancreatectomy (DP) performed by a low-volume team according to internationally accepted quality indicators and standards. Methods. Retrospective study, based on prospective data, including consecutive cases of DP due to periampullary tumors performed by the same surgical team, over a period of 4.5 years. The results were analyzed according to the main quality standards in pancreatic surgery. Results. A total of 24 cases (5.3 PD per year) were included. Two patients received neoadjuvant treatement. The median surgical time was 7.1 hours. For pancreatic adenocarcinoma (n=15), according to the current definition, R1 resection (? 1 mm) occurred in 6 cases. For the rest of the periampullary tumors (n=9), the margins of resection were free (without microscopic contact) in all cases. The lymph node harvest had a median of 14.5 nodes. Twelve patients had mild to moderate postoperative complications, only in 1 case there was a serious complication. Two cases required reoperation. Clinically relevant pancreatic fistula occurred in 4 cases. Mortality at 30 days was zero. Conclusion. Our experience shows that quality standards for PD can be achieved by a low-volume team, as long as it has adequate training and works in a high-complexity center.